Exploring the Immunological Aspects and Treatments of Recurrent Pregnancy Loss and Recurrent Implantation Failure - Garmendia, Jenny Valentina; De Sanctis, Claudia Valentina; Hajdúch, Marián; De Sanctis, Juan Bautista (International journal of molecular sciences, 2025)
Recurrent pregnancy loss (RPL) is defined as the occurrence of two or more consecutive pregnancy losses before 24 weeks of gestation. It affects 3-5% of women who are attempting to conceive. RPL can stem from a variety of causes and is frequently associated with psychological distress and a diminished quality of life. By contrast, recurrent implantation failure (RIF) refers to the inability to achieve a successful pregnancy after three or more high-quality embryo transfers or at least two instances of egg donation. RIF shares several causative factors with RPL. The immunological underpinnings of these conditions involve alterations in uterine NK cells, reductions in M2 macrophages and myeloid-derived suppressor cells, an increased Th1/Th2 ratio, a decreased Treg/Th17 ratio, the presence of shared ≥3 HLA alleles between partners, and autoimmune disorders. Various therapeutic approaches have been employed to address these immunological concerns, achieving varying degrees of success, although some therapies remain contentious within the medical community. This review intends to explore the immunological factors implicated in RPL and RIF and to analyze the immunological treatments employed for these conditions, which may include steroids, intravenous immunoglobulins, calcineurin inhibitors, anti-TNF antibodies, intralipid infusions, granulocyte colony-stimulating factor, and lymphocyte immunotherapy.
Keywords: Pregnancy; Humans; Female; lidé; Immunotherapy; HLA; Th1; Th2; recurrent pregnancy loss; Embryo Implantation; ženské pohlaví; habituální potrat; Abortion, Habitual; T regulatory cells; cytokines; recurrent implantation failure; macrophages; těhotenství; Th17; NK cells; implantace embrya; imunoterapie